Transparent Conductive Circuit
CNT hybrid transparent conductive films with metal mesh layers and chemical etching for pattern generation effectively address the challenge of achieving low sheet resistance and high transparency, enhancing the performance and reliability of transparent conductive circuits.
Patent Information
- Application Number
- JP2023178478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-11-13
- Filing Date
- 2023-10-16
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2039-11-13
AI Technical Summary
Existing transparent conductive films (TCFs) face challenges in achieving low sheet resistance while maintaining high transparency, especially for applications like antennas, and they often require wet wiping methods that can be impractical and may damage finer circuit wiring.
The use of carbon nanotube (CNT) hybrid transparent conductive films that incorporate metal mesh (MM) layers and printed CNT ink layers, where the exposed MM regions are removed by chemical etching, allowing for the generation of circuit patterns and achieving lower sheet resistance values with high transparency.
This approach enables the achievement of low sheet resistance (less than 1Ω/□) while maintaining high visible light transmittance (up to 90%), addressing the limitations of existing TCFs and improving the reliability and durability of the circuits.
Smart Images

Figure 0007659243000008 
Figure 0007659243000009 
Figure 0007659243000010
Abstract
Description
[Background technology]
[0001] The present disclosure relates to transparent conductive circuits.
[0002] Carbon nanotube (CNT) hybrid transparent conductive films (TCFs) are applied to electronic devices. Some such TCFs contain a silver nanowire (AgNW) layer and a printed CNT ink layer. A wet wiping method can be used to remove the exposed AgNW areas (i.e., areas where the CNT ink is not printed). Summary of the Invention
[0003] This disclosure relates to a CNT-based hybrid TCF that includes a metal mesh (MM) layer and a printed CNT ink layer. After the exposed MM (i.e., the areas where the CNT ink is not printed) is removed by chemical etching, a circuit pattern is generated.
[0004] The advantage of using MM over AgNWs is that lower sheet resistance values can be achieved in the transparent CNT hybrid transparent circuits while maintaining high transparency. Low sheet resistance (Rs) is important for certain applications, especially antennas. It is believed that Rs<1Ω / □(OPS) is required for printed transparent antennas to function like printed opaque metallic antennas. High transparency is also required, such as a visible light transmittance (VLT) of 85% for the printed transparent conductive film (excluding the substrate). More preferably, the VLT should be >90%.
[0005] The use of chemical etchants to dissolve exposed MM areas is an advantage when it is not practical to remove the MM using a wet wipe. For chemical etching to work, the printed CNT ink must also function as an etch mask. This makes the CNT ink a multifunctional material. Not only does the CNT ink allow for the creation of CNT hybrid (either CNT+MM or CNT+AgNW, both with polymer binders) transparent conductive films that are better than CNT or MM or AgNW alone, the CNT ink also allows for the use of standard flexible printed circuit processing methods (using chemical etchants to dissolve conductive areas not covered by the etch mask).
[0006] It may also be beneficial to use chemical etchants to create circuits that include an AgNW layer with CNT ink printed on top. The wet wiping process is not commonly accepted in the flexible printed circuit industry, which typically uses chemical etchants that are sprayed on or dipped into. The wet wiping process may leave AgNWs on top of the circuit pattern, which may cause long-term reliability issues. In addition, the wet wiping process requires some force to wipe effectively, which may damage finer circuit traces, for example, those on the order of 100 microns wide. It is also easier to etch fine gaps (100 microns or less) than using wet wiping, and this etching method is more likely to remove 100% of the AgNWs from the gap area, preventing the risk of crosstalk between adjacent circuit features.
[0007] All examples and features given below can be combined in any way that is technically possible.
[0008] In one embodiment, a transparent conductive film (TCF) includes a substrate having a surface, a metal mesh layer on at least a portion of the surface of the substrate, and a conductive layer on the metal mesh layer, the conductive layer including carbon nanotubes (CNTs) and a binder.
[0009] Some examples include one or any combination of the above and / or following features. The TCF may further include a second metal layer between the metal mesh layer and the conductive layer. The second metal layer may include a copper layer. The copper layer may be electroplated onto the metal mesh layer. The sheet resistance of the TCF may be 1 Ω / □(OPS) or less.
[0010] Some examples include one of the above and / or the following features, or any combination thereof. The combination of the metal mesh layer and the conductive layer may have a visible light transmittance (VLT) of at least 85%. The combination of the metal mesh layer and the conductive layer may have a VLT of at least 90%. The metal mesh layer includes a network of interconnected metal wires with open spaces between the wires. The network can be in a diamond, hexagon, rectangle, or random pattern. The metal mesh layer may include at least 90% open spaces. The line width of the metal wires may be 30 microns or less. The open spaces of the metal mesh layer may have a width at least 15 times the width of the metal wires. The TCF defines a circuit having conductive lines with a width, and the width of the conductive lines may be at least 10 times the width of the open spaces of the metal mesh. The metal mesh may include two different metals, a first metal and a second metal, with the second metal on top of the first metal. The first metal may include silver and the second metal may include copper.
[0011] Some examples include one or any combination of the above and / or following features: The CNTs in the conductive layer may comprise a network with an areal density of about 1-10 mg / m2. The binder:CNT ratio in the conductive layer may be greater than 120:1.
[0012] In another aspect, a method of manufacturing a TCF includes providing a substrate having a surface, depositing a metal mesh layer or a nanowire layer on at least a portion of the surface of the substrate, and patterning a conductive layer on at least a portion of the metal mesh layer on the nanowire layer, the conductive layer comprising carbon nanotubes (CNTs) and a binder.
[0013] Some examples include one or any combination of the above and / or below features. The method may further include depositing a second metal layer on the metal mesh layer prior to patterning the conductive layer. The method may further include etching exposed metal mesh layer or nanowire layer not covered by the conductive layer. Etching may be accomplished by spraying an etching solution onto the TCF. The etching solution may include ferric nitrate. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a schematic side view of the TCF. [Diagram 2] 2A-2D show a method for making a TCF. [Diagram 3] 1 shows the steps in the process of making TCF. [Figure 4] 4A-C are three images of the TCF at different magnifications. [Diagram 5] FIG. 13 shows the effect of copper plating on the metal mesh of TCF. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The CNT-based hybrid TCF 10, FIG. 1 , includes a MM layer 13 containing metal traces 14-16 and an overlying CNT ink layer 18 that bonds to the top surface of the substrate 12 and encapsulates the MM layer 13 with a conductive medium. After the exposed MM (i.e., areas where the CNT ink is not printed) is removed by chemical etching, the circuit pattern is generated.
[0016] 2A-2D show the results of a process for making a TCF of the present disclosure. It should be noted that the dimensions and other aspects of FIGS. 2A-2D are not to scale and may be exaggerated for illustrative purposes only. A practical example is provided below. Assembly 20, FIG. 2A, includes a substrate 22 carrying a MM including traces 24-27. The MM can be fabricated on the substrate by various means described herein. The MM may also include various conductive materials (e.g., metals), as further described herein. The MM is comprised of a series of thin traces (lines) that are electrically connected. The traces are typically, but not necessarily, laid out in a regular pattern (such as the hexagonal pattern shown in FIG. 4A).
[0017] 2B shows a further assembly 30 in which the MM has been overplated with a second metal (in this non-limiting example, the second metal is copper). Thus, traces 24-27 are covered by a generally thicker second metal layer including portions 34-37 to produce thickened, less porous MM traces 40-43, respectively.
[0018] Figure 2C shows a further assembly 50 in which a CNT ink 48 is printed or otherwise disposed over some or all of the MM layer shown in Figure 2B. In this figure, ink 48 is printed over traces 41, 42 but not over traces 40, 43. Thus, traces 41, 42 are covered by a conductive medium forming conductive lines or regions 49, while traces 40, 43 are exposed.
[0019] 2D shows the final TCF 60 after the exposed traces 40, 43 have been etched away, as described in more detail elsewhere herein, leaving conductors 49 on the substrate 22.
[0020] One exemplary method 70 for producing TCF is shown in FIG. 3. In step 72, a suitable substrate is prepared. In step 74, a metal mesh is printed on the surface of the substrate. In step 76, a second metal (e.g., copper) is plated onto the metal mesh. Step 76 is optional, and it may not be necessary to increase the thickness (i.e., height) of the MM lines, as the MM itself would have acceptable Rs. The plated additional metal increases the volume of the MM traces, thus decreasing their resistance. It may also help make the thin MM more robust and improve bonding with the conductive ink. In step 78, a conductive medium (referred to as "ink") is printed onto selected areas of the MM to form part of the circuitry. In one example, the ink includes carbon nanotubes as its conductive medium, and also includes a binder. CNT inks are further described elsewhere herein. The final step 80 is intended to etch the exposed MM / copper, leaving only the circuitry on the substrate.
[0021] The present disclosure will be described in more detail in some non-limiting examples given below. The examples show TCFs and aspects of their manufacture. The parameters of the TCFs and the methods of manufacture of the TCFs include:
[0022] The metal mesh may be considered as a metal grid composed of very fine lines that provide electrical conductivity through the interconnected lines while simultaneously allowing VLT through the spaces between the lines. The metal mesh can be fabricated on the surface of the substrate by any viable method including, but not limited to, direct printing, embossing, photopatterning followed by etching, and printing followed by plating. The metal mesh can be fabricated in a width sufficient for the final application of the TCF. The width can be up to 12 inches, 24 inches, or even larger.
[0023] The width of the metal lines that comprise the MM depends on the method of manufacture of the MM (some methods can produce finer line widths) and the requirements of the application (some applications, such as touch screens, need to be small enough to be invisible to the naked eye). Coarse MMs typically have line widths of about 25-50 μm. Fine MMs typically have line widths of about 2-10 μm. To make the line width relatively inconspicuous, it needs to be smaller than about 6 μm.
[0024] The spacing between metal lines depends on the desired visible light transmittance (VLT), metal line width, and metal grid pattern (e.g., hexagonal, rectangular, random, etc.). The metal lines are thick enough to have a substantially negligible VLT (i.e., they absorb or reflect almost all light). Thus, the VLT of the MM is primarily defined by the aperture ratio of the metal grid pattern. The spacing between metal lines is calculable for various shapes of metal grid pattern for a given metal line width and VLT target. For a coarse MM with a line width of 30 μm and an aperture ratio of 90%, the spacing between metal lines is approximately 550 μm for both hexagonal and square grid patterns. For a finer MM with a line width of 5 μm and an aperture ratio of 90%, the spacing between metal lines is approximately 91 μm for both hexagonal and square grid patterns.
[0025] Table 1 shows the spacing calculations for various combinations of aperture ratio and metal line width, which are examples and not limitations or definitions. [Table 1]
[0026] The required metal thickness depends on the volume resistivity of the metal, the aperture ratio, and the target sheet resistance of the MM.
[0027] For a MM with a metal volume resistivity of 4 μΩ·cm (typical for flexographic nano silver inks), a metal grid thickness of 0.15 μm, and an aperture ratio of 90%, the sheet resistance of the MM is 6 Ω / □. For the sheet resistance of the MM to be 1 Ω / □ or less (which has been found to be highly desirable for antenna and RF shielding applications), the metal grid thickness must be 0.9 μm or more. For a metal grid with an aperture ratio of 85%, the metal grid thickness required to achieve a sheet resistance of 1 Ω / □ or less is 0.6 μm or more. For a metal grid with an aperture ratio of 95%, the metal grid thickness required to achieve a sheet resistance of 1 Ω / □ or less is 1.8 μm or more.
[0028] The literature value for volume resistivity of copper is 1.72 μΩ·cm, and for silver the volume resistivity is 1.59 μΩ·cm. Both of these are lower than the typical values achieved with electroplated copper and flexographically printed nanosilver due to the porosity of the plated or printed lines. However, to achieve the copper literature value for volume resistivity of the fabricated metal grid, the thickness of the metal grid required to achieve a sheet resistance of 1 Ω / □ or less would be 0.4 μm or more.
[0029] Commercial methods for fabricating metal grids include direct printing, embossing, and photopatterning followed by etching. Most commercial methods for fabricating MMs cannot achieve sufficient metal thickness to achieve sheet resistances below 1 Ω / □ for metal grids with aperture ratios in the range of 85-95%. The thickness of the metal grid can be increased by electroplating or other viable processes.
[0030] To achieve such low sheet resistance for MMs with such a high percent aperture, the material that makes up the grid must have a very low volume resistivity, making metal the only practical material. Table 2 shows the volume resistivity of various materials in Ω·m. To convert these values to μΩ·cm, take 10 8 It is necessary to multiply it by [Table 2]
[0031] Some metals have volume resistivities below about 10 μΩ·cm. The higher volume resistivity has significant consequences, as it increases the thickness of the metal required to achieve a sheet resistance of 1 Ω / □ or less. This increases the cost of manufacturing the MM and the cost of etching the MM when patterning the circuit. Metals with literature values for volume resistivity greater than twice that of copper are presumed to be of little practical use. Applying this selection criterion to the table above, the only metals that would be selected are copper, silver, aluminum, and gold. Interestingly, these are all metals commonly used in the manufacture of printed circuits.
[0032] Another selection criterion is the ability to etch the MM with a commercially viable etchant. It is technically possible to etch gold with aqua regia, but it is not commercially practical. Silver is usually etched with ferric nitrate. Copper is usually etched with ferric chloride, but it is also possible to etch it with ferric nitrate (the same etchant used for silver). Aluminum is typically etched with sodium or potassium hydroxide. Thus, from an etching standpoint, silver, copper, and aluminum all appear to be commercially viable MM compositions. The CNT ink formulation used in the examples was also found to be suitable as an etch mask material for all of the typical etchants used for silver, copper, and aluminum. It is also noted for reference that MMs made by printing nanosilver ink followed by electroplating of copper were successfully etched with a single etchant, ferric nitrate. This makes the manufacturing process more cost-effective than requiring two separate etching processes.
[0033] With regard to the CNT ink formulation, the polymer binder type must be soluble in the ink vehicle (ideally soluble in alcohol), have good adhesion to the substrate, have high VLT and low haze, be as colorless as possible, be able to encapsulate the CNTs and MM as well, and be chemically resistant to the etchants that may be used to etch the MM (i.e., allow the CNT ink to act as an etch mask). The ability of the CNT ink to act as an etch mask also depends on the ratio of binder to CNTs in the CNT ink. Too little binder may render the CNT ink inadequate as an etch mask; it may not adequately protect the underlying MM when exposed MM areas (areas not covered by the CNT ink) are being etched. Too much binder may impair the ability of the CNTs to establish good electrical contact with each other and / or the underlying MM, and / or the surface of the circuit (to achieve low contact resistance with the printed interconnects).
[0034] Using ink vehicle chemistry similar to that of the international patent application incorporated herein by reference, a CNT concentration of 0.1 g / L was prepared in an acrylic copolymer binder (DSM B890) at 30 mg / m 2 CNT ink printed at ink coverage of 1000 nm was found to work well as an etch mask with a binder:CNT ratio of 240:1. Ratios of 60:1 and 120:1 were not fully acceptable (i.e., the underlying MM was etched away). A ratio of 180:1 was marginal (sometimes OK, but not always), and 240:1 did not appear to impair the electrical connectivity of the CNTs. Ratios higher than 240:1 are believed to be acceptable, with the upper limit being the percolation limit of the CNTs in this binder system, estimated to be about 0.2 wt% CNTs. This corresponds to a binder:CNT ratio of about 400:1.
[0035] Below are some examples illustrating aspects of the present disclosure.
[0036] < Comparison of 1Ω / □ AgNW type with MM type
[0037] <1Ω / □AgNW type: TCFs were fabricated using polyethylene terephthalate (PET) (125 μm) as the substrate and coated with a 2.0 wt% dispersion of silver nanowires (AgNWs) in isopropyl alcohol (IPA), with AgNWs of approximately 40 nm diameter and 15 μm length. The AgNW coating was approximately 5 inches wide by 7 inches long. The AgNW dispersion was coated onto the PET film at 632 mg / m2 AgNW coverage using a Mayer rod (40 micron wet film thickness). The coating was dried in a handheld convection dryer set at an outlet air temperature of 177 °C for approximately 30 seconds and baked in a convection oven at 105 °C for 3 minutes. After AgNW coating, the visible light transmittance (%VLT) was 45.6% (minus the VLT of the substrate) and the sheet resistance (Rs) of the assembly was 1 Ω / □. The AgNW coating was screen printed with carbon nanotube ink (using a reformulated version of VC101 single-walled CNT ink from Chasm Advanced Materials, Inc., Canton, Massachusetts, USA) using a 305 polyester mesh screen with a 2.5 inch block pattern (approximately 30 um wet film thickness). The ink was reformulated to a CNT concentration of 0.1 g / L and contained a polymer binder (e.g., modified methacrylic acid copolymer). Other binders that can be used in the present TCF are disclosed in International (PCT) Patent Application Publication No. WO2016 / 172315, the entire disclosure of which is incorporated herein by reference for all purposes. The printed CNT layer was dried in a handheld convection dryer set at an outlet air temperature of 177° C. for approximately 30 seconds and baked in a convection oven at 105° C. for 5 minutes. The samples were cooled to ambient temperature (approximately 25° C.). The samples were then doped with 10% ferric nitrate (Fe(NO 3 ) 3) aqueous solution for 30 seconds. Then, using another wash bottle, the sample membrane was sprayed with deionized water on both sides for 30 seconds. The membrane was then dabbed with a lint-free cloth to remove large water droplets and baked in a convection oven at 105°C for 1 minute. The CNT layers in this example were printed and etched with two different binder:CNT ratios (120:1, 240:1).
[0038] After screen printing and etching the CNT ink, the %VLT and Rs were 32.2% (minus the VLT of the substrate) and 1 Ω / □, respectively, in the 2.5" CNT printed area. After etching the exposed area outside the 2.5" CNT printed area, the %VLT increased to 90.0% (minus the substrate) and the sheet resistance was not measurable.
[0039] The results are summarized in Table 3 below. [Table 3]
[0040] <1Ω / □MM type:TCFs were fabricated using PET (125 μm) as the substrate and flexographically printed with silver (Ag) ink in a hexagonal pattern (30 micron lines of approximately 0.1-0.15 micron thickness, 500 micron spacing) using an anilox roll at 120 feet per minute and baked at 170°C for 5 seconds in a convection oven. The hexagonally patterned film was then bath electroplated with copper (Cu). The thickness of the overlying copper layer was approximately 0.5-1.5 microns (thus approximately 5-10 times the thickness of the MM layer). A 305 polyester mesh screen with a 2.5 inch block pattern (approximately 30 μm wet film thickness) was used to screen print the Ag patterned film with carbon nanotube ink (VC101 single-walled CNT ink from Chasm Advanced Materials, Inc.). The ink was reformulated to a CNT concentration of 0.1 g / L and contained the binders listed above. The CNT layers in this example were printed and etched at two different binder:CNT ratios (120:1, 240:1). The printed CNT layers were dried in a handheld convection dryer set at an outlet air temperature of 177°C for approximately 30 seconds and baked in a convection oven at 105°C for 5 minutes. The samples were allowed to cool to ambient temperature (approximately 25°C). The samples were then washed with 40% ferric nitrate (Fe(NO 3 ) 3 The exposed Ag-patterned film was etched by spraying it with an aqueous solution of 1,000 ppm NaOH for 15 seconds. The etchant was then removed by spraying deionized water on both sides of the sample film using another wash bottle for approximately 30 seconds. The film was then dabbed with a lint-free cloth to remove large water droplets and baked in a convection oven at 105 °C for 1 minute.
[0041] After flexographic printing of the Ag hexagonal patterns, the visible light transmittance (%VLT) was 90.6% (minus the VLT of the substrate) and the sheet resistance (Rs) was 5 Ω / □. After electroplating with Cu, the %VLT was 90.2% (minus the substrate) and the Rs was <1 Ω / □. After screen printing and etching a 240:1 binder:CNT ink, the %VLT and Rs remained at 90.6% (minus the substrate) and <1 Ω / □, respectively, in the 2.5 inch CNT pattern area. In the exposed areas outside the 2.5 inch CNT pattern area, both the %VLT and Rs increased to infinity, 99.6% (minus the base), respectively. After screen printing and etching the 120:1 binder:CNT ink, there was clear evidence that the etchant had eaten into the 2.5" CNT square area, starting at the outer boundary and working its way toward the center of the 2.5" square. In the exposed areas outside the 2.5" CNT pattern area, both %VLT and Rs increased to 99.6% (minus base) and infinity, respectively.
[0042] The results are summarized in Table 4 below. [Table 4]
[0043] A comparison of <1 Ω / □ MM vs. AgNW results using 0.1 g / L of 240:1 binder:CNT ink is shown in Table 5 below. [Table 5]
[0044] MM flexographically printed nano Ag+CNT ink+etching solution / each condition:
[0045] Square AgMM+CNT vs. Etch Time:A TCF sample was made using PET (125 μm) as the substrate, flexographically printed with silver (Ag) ink in a square mesh pattern using an anilox roll at 120 feet per minute, and baked in a convection oven at 170° C. for 5 seconds. A 305 polyester mesh screen with a 2.5 inch block pattern (approximately 30 μm wet film thickness) was used to screen print the Ag patterned film with carbon nanotube ink (VC101 single-walled CNT ink from Chasm Advanced Materials, Inc.). The ink was reformulated to a CNT concentration of 0.1 g / L and contained the binders listed above with a binder:CNT ratio of 240:1. The printed CNT layer was dried in a handheld convection dryer set at an outlet air temperature of 177° C. for approximately 30 seconds, and baked in a convection oven at 105° C. for 5 minutes. The sample was cooled to ambient temperature (approximately 25° C.). The samples were then soaked in ferric nitrate (Fe(NO)) in deionized (DI) water. 3 ) 3 ) and rinsed both sides of the membrane with deionized water using a wash bottle for approximately 30 seconds. The sample was then dabbed with a lint-free cloth to remove large water droplets and baked in a convection oven at 105 °C for 1 minute.
[0046] The initial sheet resistance (Rs) and visible light transmittance (%VLT) of the square Ag mesh printed with CNTs before etching were 88.7% (subtracting the substrate) and 4 Ω / □, respectively. The TCF in this example was prepared by etching ferric nitrate (Fe(NO)) in deionized (DI) water at various etching times (120, 60, 45, and 10 s). 3 ) 3 The specimen was immersed in a 40% by weight solution of
[0047] After etching, the Rs measurements for 120 and 60 s etch times increased to 15 and 7 Ω / □, respectively, indicating degradation of the patterned TCF film, while the %VLT remained the same at 88.7% (minus the substrate). The %VLT and Rs measurements for 45 and 10 s etch times remained the same at 88.7% (minus the substrate) and 4 Ω / □, respectively, from the initial.
[0048] MM flexographic printing nano Ag+Cu plating+CNT ink+etching solution / each condition:
[0049] Cu plating MM vs. etching solution type: TCF samples were prepared using PET (125 μm) as the substrate and flexographically printed with silver (Ag) ink in a hexagonal mesh pattern (30 micron lines, 500 micron spacing) using an anilox roll at 120 feet per minute and baked in a convection oven at 170° C. for 5 seconds. The hexagonal patterned film was then bath electroplated with copper (Cu) to a thickness of 1.0 micron while stirring. A 305 polyester mesh screen with a 2.5 inch block pattern (approximately 30 μm wet film thickness) was used to screen print the Ag patterned film with carbon nanotube ink (VC101 single-walled CNT ink from Chasm Advanced Materials, Inc.). The ink was reformulated to a CNT concentration of 0.1 g / L and contained the binders listed above with a binder:CNT ratio of 240:1. The printed CNT layer was dried in a handheld convection dryer set at an outlet air temperature of 177°C for approximately 30 seconds and baked in a convection oven at 105°C for 5 minutes. The sample was cooled to ambient temperature (approximately 25°C). The initial visible light transmittance (%VLT) and sheet resistance (Rs) of the Cu-plated Ag mesh with printed CNTs before etching were 90.6% (minus the substrate) and <1 Ω / □, respectively.
[0050] The TCFs in this example were etched using two different etchants (40% ferric nitrate, 20% ferric chloride) and their combinations. The samples were then rinsed with deionized (DI) water on both sides of the membrane using a wash bottle for approximately 30 seconds, dabbed with a lint-free cloth to remove large water droplets, and baked in a convection oven at 105°C for 1 minute.
[0051] Sample A was immersed in 40% ferric nitrate for 15 seconds. In the 2.5 inch CNT patterned area, %VLT and Rs remained at 90.6% (minus the substrate) and <1 Ω / □, respectively. In the exposed area outside the 2.5 inch CNT patterned area, both %VLT and Rs increased to 99.6% (minus the base) and infinity, respectively. There was also a ~2 mm halo of unetched material at the outer edge of the 2.5 inch CNT.
[0052] Sample B was immersed in 20% ferric chloride for 10 seconds. In the 2.5 inch CNT patterned area, %VLT and Rs remained at 90.6% (substrate subtracted) and <1Ω / □, respectively. In the exposed area outside the 2.5 inch CNT patterned area, %VLT increased to 92.9% (base subtracted), 6.7% lower than Sample A. This means that even though Rs was infinite, the exposed mesh area was not completely removed. Ferric chloride removed the halo effect seen in Sample A.
[0053] Sample C was first immersed in 40% ferric nitrate for 15 seconds, rinsed and dried as above, then immersed in 20% ferric chloride for 10 seconds, and finally rinsed and dried again as above. In the 2.5 inch CNT patterned area, %VLT and Rs remained at 90.6% (substrate subtracted) and <1 Ω / □, respectively. In the exposed area outside the 2.5 inch CNT patterned area, both %VLT and Rs increased to 99.6% (substrate subtracted) and infinity, respectively. The ferric chloride post-treatment removed the halo effect seen after the initial ferric nitrate etch.
[0054] Sample D was first immersed in 20% ferric chloride for 10 seconds, rinsed and dried as above, then immersed in 40% ferric nitrate for 15 seconds, and finally rinsed and dried again as above. In the 2.5 inch CNT patterned area, %VLT and Rs remained at 90.6% (subtracting the substrate) and <1 Ω / □, respectively. In the exposed area outside the 2.5 inch CNT patterned area, %VLT increased to 96.0% (subtracting the base), 3.6% lower than Sample A. This means that the exposed mesh area had not been completely removed, even though Rs was infinite. The ferric chloride removed the halo effect seen in Sample A.
[0055] Cu plating MM vs etching solution application method: TCFs were made using PET (125 μm) as the substrate and flexographically printed with silver (Ag) ink in a hexagonal pattern (30 micron lines, 500 micron spacing) using an anilox roll at 120 feet per minute and baked at 170° C. for 5 seconds in a convection oven. The hexagonal patterned film was then bath electroplated with copper (Cu) to a thickness of 1.0 micron while stirring. A 305 polyester mesh screen with a 2.5 inch block pattern (approximately 30 μm wet film thickness) was used to screen print the Ag patterned film with carbon nanotube ink (VC101 single-walled CNT ink from Chasm Advanced Materials, Inc.). The ink was reformulated to a CNT concentration of 0.1 g / L and contained the binders listed above at a binder:CNT ratio of 240:1. The printed CNT layer was dried in a handheld convection dryer set at 177°C outlet air for approximately 30 seconds and baked in a convection oven at 105°C for 5 minutes. The sample was cooled to ambient temperature (approximately 25°C). The initial %VLT and sheet resistance (Rs) of the CNT-printed Cu-plated Ag mesh with printed CNTs before etching were 90.6% (minus the substrate) and <1 Ω / □, respectively.
[0056] The TCF in this example was developed using two different application methods (spray and immersion) to prepare 40% ferric nitrate (Fe(NO 3 ) 3) for 15 seconds. Then, using another wash bottle, the sample membrane was sprayed with deionized water on both sides for approximately 30 seconds. The membrane was then dabbed with a lint-free cloth to remove any large water droplets and baked in a convection oven at 105 °C for 1 minute. In both cases, the %VLT and Rs of the 2.5" CNT square area remained at 90.6% (subtracting the substrate) and <1 Ω / □, respectively. Both samples showed good etching of the exposed Cu-plated mesh pattern not protected by the 2.5" CNT squares, although the immersed sample had a halo of approximately 2 mm around the perimeter of the 2.5" printed square that was not completely etched. The sprayed ferric nitrate did not show any signs of this halo.
[0057] Chemical Etching of AgNWs Formed AgeNTs:
[0058] Etching in AgeNT-75:TCFs were fabricated using PET (125 μm) as a substrate and coated with a dispersion of 0.3 wt% silver nanowire solution using an aqueous silver nanowire ink (diameter about 40 nm, length 15 μm). The AgNW coating was about 5 inches wide by 7 inches long. The AgNW dispersion was coated onto the PET film using a Mayer rod (12 micron wet film thickness) at an AgNW coverage of 28 mg / m2. The coating was dried for about 30 seconds with a handheld convection dryer set at an outlet air temperature of 177°C and baked in a convection oven at 105°C for 3 minutes. The AgNW coating was screen printed with carbon nanotube ink (VC101 single-walled CNT ink from Chasm Advanced Materials, Inc.) using a 305 polyester mesh screen with a 2.5 inch block pattern (wet film thickness about 30 μm). The ink was reformulated to a CNT concentration of 0.1 g / L and contained the above binders at a binder:CNT ratio of 120:1. The printed CNT layer was dried in a handheld convection dryer set at an outlet air temperature of 177 °C for approximately 30 seconds and baked in a convection oven at 105 °C for 5 minutes. The sample was cooled to ambient temperature (approximately 25 °C). The initial %VLT and sheet resistance (Rs) of the CNT-printed AgNW film before etching were 99.3% (minus the substrate) and 60 Ω / □, respectively.
[0059] The TCF in this example is 10% ferric nitrate (Fe(NO 3 ) 3 ) for 15 seconds. Then, using another wash bottle, the sample membrane was sprayed with DI water on both sides for 30 seconds. The membrane was then dabbed with a lint-free cloth to remove large water droplets and baked in a convection oven at 105°C for 1 minute.
[0060] After screen printing and etching the CNT ink, in the 2.5" CNT printed area, the %VLT and Rs remained at 99.3% (minus the VLT of the substrate) and 60 Ω / □, respectively. After etching, in the exposed area outside the 2.5" CNT printed area, the %VLT increased to 91.0% (the same value as the bare substrate) and the sheet resistance was not measurable.
[0061] Below is an overview of the various chemical etchants that can be used to etch copper (Cu) or silver (Ag) materials. To date, the best form for etching AgNWs or MMs has been to use ferric nitrate as the etchant, using spray or immersion techniques. This does not exclude other etchants or other etching methods currently known or developed in the future.
[0062] Review of Cu and Ag Etching Techniques:
[0063] Copper etchant: A number of wet chemistry systems (Table 6) have been used to etch Cu. Important parameters for controlling and optimizing the etching process are pH, temperature, etchant replenishment, and degree of agitation.
[0064] One of the most commonly used and least expensive chemical systems is ferric chloride. The mechanism involves the oxidation of copper to cuprous chloride. Other chemical species, such as HCl, may be added to improve the etching performance by enhancing the kinetics of cuprous chloride formation, which may be the rate-controlling step in the overall kinetics of the etching process.
[0065] Another commonly used etchant is cupric chloride. Copper is reduced to cuprous chloride, which reduces the performance of the etchant, so CuCl 2 Regeneration of the catalyst is important. As with ferric chloride, other chemicals (HCl, KCl, NaCl) are usually added to improve performance. [Table 6]
[0066] Alkaline etchants, such as ammonium hydroxide, combine with copper ions to form cupric ammonium complex ions that stabilize the dissolved Cu in solution.
[0067] Ammonium persulfate is an excellent etchant for Cu, but a heat exchanger is required as the process is exothermic. Furthermore, the etch rate is lower than some of the more aggressive chemistries, making this a good choice for processes that are more easily controlled but may also be rate controlled in the overall process scheme.
[0068] Silver Etchant: Although silver and copper are commonly used in many of the same electrical and electronic applications, the number of etchants (Table 7) that have been used for Ag compared to Cu is much smaller due to the extreme cost difference. Typical etchants for silver include nitric acid-water and sulfuric acid-water in various concentrations. [Table 7]
[0069] Additional examples:
[0070] There are numerous methods that can be used to create MM layers with various combinations of Rs and VLT properties. One method involves flexographic printing of MMs using nano-Ag inks. This method appears to be suitable for creating MMs with Rs of about 10 Ω / □ and VLTs of about 90%. To reduce the Rs of the MM without sacrificing the VLT, Cu has been electroplated onto the printed AgMM to create Ag / CuMMs. Other materials may be used for both the printed and overlying plated layers.
[0071] Other methods can be used to create the MM. This includes using more advanced flexographic printing plates to achieve MM line widths of up to about 3 microns. This example has an MM line width of about 30 microns. Reducing the MM line width makes the MM less visible at the same VLT value. Also, the thinner lines allow for thinner line widths in the CNT hybrid circuit. As a general rule of thumb, to achieve a % open area of the MM greater than about 90%, the width of the open area of the mesh needs to be about 15-20 times the MM line width. The % open area determines the maximum VLT value of the printed CNT hybrid circuit. Thus, a 30 micron MM line width should have an open area width of about 500 microns. Another general rule of thumb is that in order to place enough conductive material for the circuit wiring, the minimum line width of the printed CNT hybrid circuit needs to be at least 10 times the width of the open area segment of the MM. Thus, the minimum line width of the circuit should be greater than about 5 mm. This minimum line width is expected to be as small as 0.5 mm if the MM line width can be reduced to 3 microns.
[0072] It should also be possible to create MMs by printing a suitable catalyst (e.g., palladium) and using electroless Cu to create the MM. Metals other than Cu are possible. If Rs is not low enough, Cu electroplating after electroless Cu deposition can be used.
[0073] MMs can also be created using lithographic etching methods or various lift-off patterning methods deployed in the printed circuit industry. MMs can also be created using laser ablation of thin metal films.
[0074] Figures 4A-4C, 5A and 5B contain images illustrating the printed CNT hybrids (MM type), where the MM was flexographically printed Ag (without subsequent Cu electroplating). The SEM image in Figure 4A (50x magnification) shows the MM hexagonal pattern with Ag line widths of about 30 μm and overall width of the hexagonal open spaces of about 500 μm. The SEM image in Figure 4B (50kx magnification) shows how the CNTs form a well-connected network in a space that would normally have no conductive material. The areal density of the CNT network is sufficiently low (about 1-10 mg / m 2 ), which is transparent, but with a sufficiently high areal density allows for charge diffusion in the open spaces, resulting in a more uniform electrode. The SEM image in Figure 4C (100kx magnification) shows how the CNT network can help strengthen the porous AgMM lines and provide redundant conductive paths for increased reliability. Note that the CNT inks printed on top of the AgMM shown in Figure 4A did not contain any polymer binder in them, so the CNT network was only visible in the SEM images in Figures 4B and 4C. Typically, the polymer binder is at a sufficient level to encapsulate the MM and the CNTs, and the CNT network self-organizes within the polymer matrix. This makes it impossible to see the CNT network in SEM imaging.
[0075] The CNT network in the polymer matrix also provides electrical connectivity from the surface of the printed CNT hybrid circuit to the underlying MM, allowing for reliable and easy electrical connections to the circuit. This situation also occurs when the CNT ink is printed on top of AgNWs. In both cases, there is good electrical connectivity from the surface of the circuit to the underlying MM or AgNW layer.
[0076] Figures 5A and 5B show only flexographically printed AgMM, which is plated with copper. Figure 5A includes images at both 10k and 25k magnifications, and Figure 5B includes images at both 50k and 100k magnifications. It should also be noted that the porous appearance of the flexographically printed AgMM can be "filled" after Cu electroplating to reduce the porosity. The thickness of the Cu electroplating is about 0.5-1.5 microns, whereas the thickness of the flexographically printed Ag can be about 0.1-0.15 microns. The SEM images in Figures 5A and 5B clearly show this. It is believed that not only does the Cu plating reduce sheet resistance (without compromising VLT), but it also improves reliability since the Ag / CuMM structure is less porous than the AgMM structure alone.
[0077] The polymer binder serves to enhance the environmental stability and adhesion of the printed CNT hybrid circuits. It also serves to protect the MM or AgNWs from chemical etching (i.e., it is a component to provide an etch mask function). The binder should have good environmental stability and adhesion properties, high transparency, and low haze.
[0078] It is reasonable to expect that many different binders could be used. Selection criteria for suitable polymer binder candidates include: Good optical properties (high transparency, low haze, low coloration, refractive index similar to PET). Good adhesion to commonly used plastic film substrates (PET, PC, acrylic, etc.). ·Temperature processing requirements (<120C) compatible with plastic film substrates. Solubility compatible with ink formulations (e.g. good solubility in alcohol and / or amine components). Chemical resistance to common etchants used for Ag and Cu.
[0079] The type of CNT used in this disclosure was single-walled CNT, however, it is reasonable to expect that good results would be obtained by substituting double-, few-, or multiple-walled CNTs.
[0080] A number of implementations have been described. Nevertheless, additional modifications can be made without departing from the scope of the inventive concepts described herein, and therefore, other examples are within the scope of the following claims. The present invention can also be implemented with the following configuration. (1) a substrate having a surface; a metal mesh layer on at least a portion of a surface of the substrate; A transparent conductive film (TCF) comprising: a conductive layer comprising carbon nanotubes (CNTs) and a binder on a metal mesh layer. (2) The transparent conductive film according to (1) above, further comprising a second metal layer between the metal mesh layer and the conductive layer. (3) The transparent conductive film according to (2) above, wherein the second metal layer includes a copper layer. (4) The transparent conductive film according to (3) above, wherein the copper layer is electroplated onto the metal mesh layer. (5) The transparent conductive film according to (1) above, wherein the sheet resistance of the transparent conductive film is 1 Ω / □(OPS) or less. (6) The transparent conductive film according to (1) above, wherein the combination of the metal mesh layer and the conductive layer has a visible light transmittance (VLT) of at least 85%. (7) The transparent conductive film according to (6) above, wherein the combination of the metal mesh layer and the conductive layer has a visible light transmittance of at least 90%. (8) The transparent conductive film according to (1) above, wherein the metal mesh layer comprises a network of interconnected metal wires with open spaces between the wires. (9) The transparent conductive film according to (8) above, wherein the network has a hexagonal, rectangular or random pattern. (10) The transparent conductive film according to (8) above, wherein the metal mesh layer comprises at least 90% open space. (11) The transparent conductive film according to (8) above, wherein the line width of the metal wiring is 30 microns or less. (12) The transparent conductive film according to (8) above, wherein the open space in the metal mesh layer has a width at least 15 times the width of the metal wiring. (13) A transparent conductive film according to (8) above, defining a circuit having conductive lines having a certain width, the width of the conductive lines being at least 10 times the width of the open spaces of the metal mesh. (14) The transparent conductive film according to (1) above, wherein the metal mesh comprises two different metals, a first metal and a second metal, the second metal being on top of the first metal. (15) The transparent conductive film according to (14) above, wherein the first metal includes silver and the second metal includes copper. (16) The carbon nanotubes in the conductive layer have a surface density of about 1 to 10 mg / m 2 The transparent conductive film according to (1) above, comprising a network of the above formula: (17) The transparent conductive film according to (1) above, wherein the ratio of binder:carbon nanotubes in the conductive layer is greater than 120:1. (18) Providing a substrate having a surface; depositing a metal mesh or nanowire layer over at least a portion of a surface of a substrate; A method for manufacturing a transparent conductive film (TCF), comprising: patterning a conductive layer on at least a portion of a metal mesh layer or a nanowire layer, the conductive layer comprising carbon nanotubes (CNTs) and a binder. (19) The method according to (18) above, further comprising depositing a second metal layer on the metal mesh layer before patterning the conductive layer. (20) The method according to (18) above, wherein the nanowire layer comprises silver nanowires. (21) The method according to (18) above, further comprising etching the exposed metal mesh layer or nanowire layer not covered by the conductive layer. (22) The method according to (21) above, wherein the etching is accomplished by spraying an etching solution onto the transparent conductive film. (23) The method according to (22) above, wherein the etching solution contains ferric nitrate.
Claims
1. Providing a substrate having a surface; depositing a metal mesh layer over at least a portion of a surface of a substrate; depositing a second metal layer over the metal mesh layer; A method for manufacturing a transparent conductive film (TCF), comprising: patterning a conductive layer on at least a portion of the metal mesh layer on which the second metal layer is deposited, the conductive layer comprising carbon nanotubes (CNTs) and a binder.
2. 10. The method of claim 1, further comprising etching the exposed metal mesh layer on which the second metal layer is deposited that is not covered by the conductive layer.
3. 3. The method of claim 2, wherein the etching is accomplished by spraying an etching solution onto the transparent conductive film.
4. 4. The method of claim 3, wherein the etching solution comprises ferric nitrate.
5. The method of claim 1, wherein the second metal layer comprises a copper layer.
6. The method of claim 5, wherein the copper layer is electroplated onto the metal mesh layer.
7. The method described in claim 1, characterized in that the sheet resistance of the transparent conductive film is 1 Ω / □ (OPS) or less.
8. The method of claim 1, wherein the combination of the metal mesh layer, the second metal layer and the conductive layer has a visible light transmittance (VLT) of at least 85%.
9. The method of claim 1, wherein the combination of the metal mesh layer, the second metal layer and the conductive layer has a visible light transmittance of at least 90%.
10. The method of claim 1, wherein the metal mesh layer comprises a network of interconnected metal wires having open spaces between the wires.
11. The method of claim 10, wherein the network is a hexagon, a rectangle, or a random pattern.
12. The method of claim 10, wherein the metal mesh layer comprises at least 90% open space.
13. The method of claim 10, wherein the line width of the metal wiring is 30 microns or less.
14. The method of claim 10, wherein the open spaces in the metal mesh layer have a width at least 15 times the width of the metal wiring.
15. The method of claim 10, wherein the network includes a circuit having conductive lines having a width, the width of the conductive lines being at least 10 times the width of the open spaces of the metal mesh.
16. The method of claim 1, wherein the metal mesh comprises silver and the second metal comprises copper.
17. The method of claim 1, wherein the carbon nanotubes in the conductive layer comprise a network having an areal density of about 1-10 mg / m 2 .
18. The method of claim 1, wherein the ratio of binder:carbon nanotubes in the conductive layer is 240:1 or greater.
Citation Information
Patent Citations
Electric conductor with improved surface resistance and method for producing the same
JP2016062653A
Production method of transparent wiring member and transparent wiring member
JP2016197554A
transparent conductive film
JP2018524788A